Representasi Kehidupan Geisha Dalam Film Memoirs of A Geisha - Amalia, Kartika (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
Geisha are traditional Japanese artist-entertainers.  Therefore, this research aims to represent the life of a Geisha in Memoirs of a Geisha movie, using Charles Sanders Peirce’s theory of semiotic analysis, to see the representation of the life of a Geisha in Memories of a Geisha movie.  By using qualitative research that uses descriptive methods.  The results of his research show that the life of a Geisha is not easy, to the point that even before becoming a Geisha someone has to undergo difficult training, Geisha must also be able to have skills such as dancing and playing musical instruments.